2012
DOI: 10.1111/j.1475-6773.2012.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Illness and Patient Satisfaction

Abstract: Providers seeking to improve their patient satisfaction scores could do so by considering patient characteristics when accepting new patients or deciding who to refer to other providers for treatment. However, our findings suggest constructive actions that providers can take to improve their patient satisfaction scores without selection on patient characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 41 publications
2
55
3
Order By: Relevance
“…The association between gender and patients' preference for involvement in the decision-making process is variable (Garfield et al, 2007). Females are more interested than males in having a participatory role as well as more satisfied with the care provided (Arora & McHorney, 2000;Carlin et al, 2012;Levinson, Kao, Kuby, & Thisted, 2005;Nease Jr, 1995). Other studies show no significant association between gender and patients' preference for decision sharing with physicians (Florin, Ehrenberg, & Ehnfors, 2006;McKinstry, 2000).…”
Section: Patient Sociodemographic Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between gender and patients' preference for involvement in the decision-making process is variable (Garfield et al, 2007). Females are more interested than males in having a participatory role as well as more satisfied with the care provided (Arora & McHorney, 2000;Carlin et al, 2012;Levinson, Kao, Kuby, & Thisted, 2005;Nease Jr, 1995). Other studies show no significant association between gender and patients' preference for decision sharing with physicians (Florin, Ehrenberg, & Ehnfors, 2006;McKinstry, 2000).…”
Section: Patient Sociodemographic Factorsmentioning
confidence: 99%
“…Researchers have shown that as patients age, they become less interested in participating in the health decision-making as well as less inclined to engage in effective communication with their physicians (Garfield, Smith, Francis, & Chalmers, 2007; Morgan, 2003;Robinson et al, 2006;Schneider et al, 2006). Paradoxically, one study found that older patients are more likely to be satisfied with the care provided (Carlin, Christianson, Keenan, & Finch, 2012). Patients of high educational and social status were more likely to engage in the consultation by asking questions and inquiring about other treatment options in comparison to patients with a lower socioeconomic status (Garfield et al, 2007;Morgan, 2003;Schneider et al, 2006).…”
Section: Patient Sociodemographic Factorsmentioning
confidence: 99%
See 3 more Smart Citations